Theoretical dimensions of enterprise competitiveness – economic and social aspect - Bielienkova, O.; Molodid, O. (Ways to Improve Construction Efficiency, 2022)
The article conducted a thorough study of theoretical and methodological approaches to measuring the competitiveness of construction enterprises as a complex economic category, reflecting the ability of the enterprise to function effectively in the market, attract investments, adapt to changes in the environment and ensure long-term profitability. In the conditions of transformations of the economy, unstable institutional environment, increasing competition, in particular as a result of the implementation of large -scale programs for the restoration of infrastructure in Ukraine, the problem of determining the real level of competitiveness of the enterprises of the construction sector is of particular relevance.The content of the concept of "competitiveness of a construction enterprise" from the standpoint of system and resource-functional approaches is specified, which allows to take into account both internal characteristics (resource potential, technological level, quality of management, financial stability), and external factors of influence (industry trends, regulatory environment, market.A comparative analysis of existing methodological approaches to the evaluation of competitiveness, in particular parametric, rating, matrix and integral, has been carried out. The advantages and restrictions of each of them are determined, taking into account the industry specificity of construction. The need for complex multifactorial evaluation, which includes financial, economic, production, technological, marketing, personnel and organizational and management indicators, is substantiated. The generalized structure of indicators is proposed, which allows to formalize the level of competitiveness using the integral coefficient, taking into account the weight of each criterion.Particular attention is paid to the construction of the author's model of competitiveness assessment, which allows both a comparative analysis between enterprises and monitoring of internal dynamics over time. The model takes into account the specific market risks of the construction industry, the level of innovative development of the enterprise, its participation in public-private partnerships, reputation capital and the ability to attract funding.